Renewable energy strategy in Hungary - Török, Imre (Acta Agraria Debreceniensis, 2014)
The price of energy determinates our daily life. It is very necessary that we make energy strategy such as effective in everyday life, furthermore appoint a predictable development path. In these energy strategies the renewable energy and the energy efficiency is highlighted. This article describes about relevant pledges from recent years and possible improvements.